A Research on the Chronic Effects of Training at High Altitude on Some Physical Characteristics and Some Blood Parameters of the Students from Kastamonu School of Physical Education and Sports - İsmail Kaya; Kadir Gökdemir (ümit doğan üstün, 2015)
The purpose of this study was to compare the alternations of physical performance, some blood parameters, pulse and blood pressure of male student athletes from Kastamonu School of Physical Education and Sports. 15 student athletes volunteered for the study. The sampling group trained for two hours between 9.00-11.00 a.m. The sampling groups' RBC, WBC, Hb, HCT, resting systolic blood pressure, resting diastolic blood pressure, resting heart rate and aerobic and anaerobic values on the fifteenth day at high altitude (3250 m) and on the seventh day after returning sea level were measured. T- test was used as a statistical method and significance level was determined as (P<0.05). The results showed that, WBC, HB, resting systolic blood pressure, resting diastolic blood pressure, resting heart rate, score were significantly different (p<0.05) but there was no significant difference between RBC, HCT, aerobic and anaerobic values (P>0.05). The results suggest that athletes who trained at high altitude should be supplied by vitamin and minerals, they should sleep and rest regularly, they shouldn't make any exercise which can cause to lactic acid accumulation.